Correlation study between total calcium, ionized calcium, serum albumin and their significance with Vitamin D. - Rajaraman, Srinath; Selvanayagam, Swaminathan; Chidambaram, Ramalingam (Journal of Experimental Sciences, 2012)
Calcium is an essential but controversial nutrient: there is no consensus on the level of human calcium requirement or the significance of calcium deficiency. Apart from providing rigidity to the skeleton, an alternate metabolic form of calcium viz., ionized calcium plays a key role in the biochemical and metabolic functions. The protection of this critical concentration by parathyroid hormone and vitamin D reflects the vital role that calcium plays in the neuromuscular system in regulation of the heart, in enzyme-mediated reactions and in many other metabolic processes. The objective of this study was to examine and establish the relationship between Total Calcium, Ionized Calcium and Serum Albumin and the significance of these factors with Vitamin D. For the samples, biochemical assay using electro-chemiluminescence technique (for Vitamin D) was used; Total Calcium and Serum Albumin were analyzed using manual dye-binding methods and the readings were acquired using a semi automatic analyzer. Appropriate statistical methods were used to conclude that, a very good correlation exists between Total calcium to VitaminD3 to that of Ionized Calcium to Vitamin D3 (P<0.0001) and similar correlation was also observed when the ratio of ionized calcium to albumin was compared. On the whole our study strongly recommends the measurement of all the four parameters for effective diagnosis of Calcium and Vitamin D related disorders.